PANDANGAN PENGAKUAN IMAN NICEA-KONSTANTINOPEL (KREDO NICEA) TENTANG DOKTRIN ALLAH TRITUNGGAL - Hendi H (Institut Agama Kristen Negeri Tarutung, 2019)
AbstractThe article describes the doctrine of the Holy Trinity according to the views of the Church Fathers formulated in a Nicene and Constantinople Creed (Nicene Creed). There are many errors and debates about this doctrine throughout the ages including today. This article is important because it puts the right theological foundation, which is orthodox understanding (straight teaching) about the Trinity. The author will describe the 8 points of the Nicene Creed and interact with the Scriptures and the writings of the Church Fathers. The Holy Trinity is essentially One God in Three Persons or Three Persons in One Essence or the Essence of God, namely the Father is God, the Son is God, and the Holy Spirit is God so the Trinity God does not speak about the number of God but the existence of God . It is called the Father because He is the source of everything including the Son who is His Word begotten or comes out from the Father and the Holy Spirit which is the breath or source of life from the Father himself. The Word and the Holy Spirit are a necessity in the FatherKey words: Trinity, Father, Son, Holy Spirit, Nicea, Constantinople, Father of Church, Essence